ANALISIS POTENSI PENERIMAAN PAJAK DAN STRATEGI KEBIJAKAN UNTUK MENGOPTIMALKAN PAJAK HOTEL DI KABUPATEN BANYUWANGI - Puspita, Yeni; Wicaksono, Galih (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose-Thus research aims to calculate the potential of hotel tax revenue and how policy strategies to optimize hotel tax revenue in Bnayuwangi Regency Design/methodology/approach-This study calculates the magnitude of the hotel tax potential in the Banyuwangi Regency, using a quantitative approach. The sample is taken in each district that has a hotel tax object Findings- Based on field findings in 16 districts that have hotel tax objects, were sampled at 2 hotels in each district, potentials found was Rp. 19,004,102,434. Based on the 2018 realization and target data, the hotel tax target is Rp 1,840,000,000 and the realization is 3,368,454,736. It indicates the potential for lost tax revenue from hotel in Banyuwangi Regency. Implications-Strategies that can be done to optimize revenue are by simplifying the taxation system, providing services to taxpayers, and controlling the administration. Keywords: Tourism, Hotel Tax, Potency, Policy Strategy